Biocompatibility of Chitosan/Collagen/PVA Nanocomposite Containing Calcium Apatite - Basuki Wirjosentono; M. Dimas Ekananda Dawandono; Tamrin Tamrin (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
Biopolymer-based nanocomposites containing bone minerals have been used intensively as bone- graft in various broken bone accidents. Main objective of this work is to prepare and characterise biocompatible chitosan/collagen/PVA nanocomposites containing calcium apatite suitable for bone-graft engineering. The calcium apatite nanofillers were prepared by calcination of cow bones at 830oC for 3 hours, followed by ball-milling and ultrasonication processes and characterization using particle size analysis (PSA) and electron scanning microscopy (SEM). It was found that particle siz of   the   filler  ranging  between  100-8000  nm   due   partial  aglomersation.  The   bone-graft nanocomposites specimens were prepared with various calcium apetite loading (0-10%) in constant ratio (1:1:1) of chitosan/collagen/PVA biopolymers. Compression strength of the nanocomposites containing optimum filler of 6% was found 2.01 MPa, its density was 1.19 g/cm3  and its water absorption capacity 58.3% and biodegradation rate 2.67%/day. Degree of biocompatibillity of the bone-graft was revealed after its implementation in mice tissue which did not show any histopathological effect after 14 days.